Clinical and laboratory efficacy of repetitive triamcinolone injections in carpal tunnel syndrome - Ceylan, Mustafa; Simsek, Fatma; Riza Sonkaya, Ali (Annals of Medical Research, 2021)
None
Keywords: Carpal Tunnel Syndrome; Entrapment Neuropathy; Pain severity; Steroid Injection; Triamcinolone Injection; Nerve conduction study.